Pengaruh Akuntabilitas Pengelolaan Dana Desa, Kompetensi Aparat Desa, Pengendalian Internal, Dan Sistem Informasi Akuntansi Berbasis SISKEUDES terhadap Kepercayaan Masyarakat - Meliyanti, Devi; Febri Darmayanti, Elmira; Septiani, Ana (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze the effect of village fund management accountability, village apparatus competence, internal control, and Siskeudes-based accounting information system on public trust. This study used a quantitative approach with multiple linear regression methods and was processed using spss. The sample in this study was 117 residents of Bulu Sari Village who were taken using cluster sampling techniques. The results of the study indicate that partially, accountability in village fund management, internal control, and Siskeudes-based information systems have a significant effect on public trust, while the competence of village officials does not have a significant effect. Simultaneously, the four variables have a significant effect on public trust in the village government.